Implementasi Program Pembinaan Sepak Bola Berbasis Turnamen Edukatif untuk Meningkatkan Sportivitas Siswa SMA Se-Provinsi Gorontalo - Meyke Parengkuan; Rifky Mile (Jambura Arena Pengabdian, 2026)
This community service program aimed to enhance the sportsmanship of senior high school students through the implementation of an educational football tournament-based coaching program in Gorontalo Province, Indonesia. The program was conducted from 12 April to 3 June 2026, involving 18 senior high schools and 324 students. A participatory approach was employed through four stages: program socialization, sportsmanship education, implementation of an educational football tournament, and program evaluation. Data were collected using a validated and reliable sportsmanship questionnaire supported by direct observations during the matches. Program success was determined based on three indicators: a minimum 15% increase in sportsmanship scores, at least 80% of participants achieving good to very good sportsmanship categories, and a reduction in unsportsmanlike behavior during the tournament. The results demonstrated that the average sportsmanship score increased from 42 to 49 (17%), while the proportion of participants classified as having good to very good sportsmanship increased from 55% to 83%. Observational findings also revealed fewer protests against referees, fewer intentional fouls, and reduced player conflicts throughout the competition. In addition to improving students' sportsmanship, the program produced a sportsmanship coaching module, activity documentation videos, and recommendations for a school-based sport character education model. These findings indicate that educational football tournaments provide an effective community engagement model for integrating sports competition with character education to strengthen students' sportsmanship.